PENERAPAN PERATURAN KEJAKSAAN NOMOR 18 TAHUN 2021 TERKAIT REHABILITASI NARKOTIKA BERDASARKAN KEADILAN RESTORATIF - Hastuti, Ari; Sriwidodo, Joko; Basuki, Basuki (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Restorative Justice is utilized as an approach to resolve criminal cases involving offenders, victims, families, and relevant parties to seek a fair resolution, prioritizing rehabilitation over retribution. The Guidelines for Narcotics Rehabilitation based on Restorative Justice guide Prosecutors in the stages of pre-prosecution, prosecution, and rehabilitation supervision. In practice, there are differences in the interpretation and application of the dominus litis principle by Prosecutors in handling narcotics cases with a restorative justice approach. The limitations in understanding and applying the dominus litis principle can affect the consistency and uniformity of rehabilitation policies provided by the Prosecutor's Office in narcotics criminal cases. Moreover, this issue can also lead to inconsistent treatment of narcotics defendants in need of rehabilitation. The issue concerning the authority of the prosecutor's office in implementing rehabilitation policies in narcotics criminal cases with a restorative justice approach and enforcing the law in narcotics criminal cases with a restorative justice approach. This research method employed a normative juridical research type using legislative and conceptual approaches as the basis for analysis in addressing the issues. The conceptual approach used includes the concept of narcotics rehabilitation by the Indonesian Prosecutor's Office based on theories of authority and law enforcement, serving as analytical tools in addressing the issue of prosecutor's authority in law enforcement rehabilitation in narcotics criminal cases. In conclusion, the Prosecutor's Office has the juridical authority to conduct rehabilitation in narcotics criminal cases with a restorative justice approach. This is regulated in the Indonesian Prosecutor's Regulation Number 18 of 2021. Prosecutors play a central role in controlling cases, from investigation to court judgment execution, based on the dominus litis principle. Public prosecutors have a significant role in ensuring that medical and social rehabilitation efforts are carried out appropriately by designated rehabilitation institutions or health services, as well as in issuing warnings and taking further action if suspects fail to comply with the prescribed rehabilitation process. Law enforcement in cases of narcotics abuse requires a thorough understanding and strict application of the requirements based on the Indonesian Prosecutor's Regulation Number 18 of 2021